Increased Levels of Interleukin-36 in Obesity and Type 2 Diabetes Fuel Adipose Tissue Inflammation by Inducing Its Own Expression and Release by Adipocytes and Macrophages - Frühbeck, Gema; Gómez-Ambrosi, Javier; Ramírez, Beatriz; Mentxaka, Amaia; Rodríguez, Amaia; Becerril, Sara; Reina, Gabriel; Valentí, Victor; Moncada, Rafael; Silva, Camilo; Catalán, Victoria (Frontiers in Immunology, 2022)
Interleukin (IL)-36 is a recently described cytokine with well-known functions in the regulation of multiple inflammatory diseases. Since no data exists on how this cytokine regulates adipose tissue (AT) homeostasis, we aimed to explore the function of a specific isoform, IL-36g, an agonist, in human obesity and obesity-associated type 2 diabetes as well as in AT inflammation and fibrosis. Plasma IL-36g was measured in 91 participants in a case-control study and the effect of weight loss was evaluated in 31 patients with severe obesity undergoing bariatric surgery. Gene expression levels of IL36G and its receptor were analyzed in relevant human metabolic tissues. The effect of inflammatory factors and IL-36g was determined in vitro in human adipocytes and macrophages. We found, for the first time, that the increased (P<0.05) circulating levels of IL-36g in patients with obesity decreased (P<0.001) after weight and fat loss achieved by Roux-en-Y gastric bypass and that gene expression levels of IL36G were upregulated in the visceral AT (P<0.05) and in the peripheral blood mononuclear cells (P<0.01) from patients with obesity. We also demonstrated increased (P<0.05) expression levels of Il36g in the epididymal AT from diet-induced obese mice. IL36G was significantly enhanced (P<0.001) by LPS in human adipocytes and monocyte-derived macrophages, while no changes were found after the incubation with anti-inflammatory cytokines. The addition of IL-36g for 24 h strongly induced (P<0.01) its own expression as well as key inflammatory and chemoattractant factors with no changes in genes associated with fibrosis. Furthermore, adipocyte-conditioned media obtained from patients with obesity increased (P<0.01) the release of IL-36g and the expression (P<0.05) of cathepsin G (CTSG) in monocyte-derived macrophages. These findings provide, for the first time, evidence about the properties of IL-36g in the regulation of AT-chronic inflammation, emerging as a link between AT biology and the obesity-associated comorbidities.